Synthesis Characterization and Antimicrobial Activity Studies of Some Transition Metal Complexes Derived from 3-Chloro-N′-[(1E)-(2-hydroxy phenyl)methylene]-6-methoxy-1-benzothiophene-2-carbohydrazide - Vivekanand D. Biradar; B. H. M. Mruthyunjayaswamy (The Scientific World Journal)
A series of new coordination complexes of Cu(II), Co(II), Ni(II), Zn(II), Hg(II), Mn(II), and Fe(III) with the Schiff base 3-chloro-N′-[(1E)-(2-hydroxy phenyl)methylene]-6-methoxy-1-benzothiophene-2-carbohydrazide (HL) have been synthesized and characterized by elemental analysis, electrical conductivity measurements, IR spectra, 1H NMR, mass spectral data, electronic spectra, magnetic susceptibility, ESR spectra, TGA, and Powder XRD data. The Schiff base behaves as tridentate ONO donor ligand and forms the complexes of the type ML2 (metal-ligand) stoichiometry for Cu(II), Co(II), Ni(II), and Mn(II) complexes and ML stoichiometry for Zn(II), Hg(II), and Fe(III) complexes. All the complexes are colored and nonelectrolytes. It is found that Cu(II), Co(II), Ni(II), Mn(II) and Fe(III) complexes have exhibited octahedral geometry whereas Zn(II) and Hg(II) complexes exhibited tetrahedral geometry. The ligand and its metal complexes have been screened for their antibacterial activity against E. coli and S. aureus and antifungal activity against A. niger and A. flavus.